Spatial Analysis of Distribution Pattern of Covid-19 Cases in Batang Regency - Harsritanto Bangun I R (EDP Sciences, 2021)
The pandemic of covid-19 had brought many responses from every institution. As one of the religious institutions, Mosque was reported various adaptations in aims to support their activities. The adaptations were related to strategies in physical designs, health protocols implementations, and embedded technologies. The interaction between each strategy also shown different patterns of mosques’ innovation in serving their communities. These mosque studies consist of literature reviews and site observations to elaborate the communal mosque adaptations against the pandemic. The shifting of mosques is closely related to environments and technologies.